PENGARUH CORPORATE GOVERNANCE DAN FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Luh Gde Novitasari (Faculty of Economics and Business, Universitas Warmadewa, 2017)
Abstract This research aims to test the influence of corporate governance and fundamental factor against the return of stock. The population of this research are companies listed on the Indonesia stock exchange of the year 2013-2015, whereas the sample in this research as much as 18 companies. Method of determination of the sample used is purposive sampling. Data analysis technique used was multiple linear regression analysis. The results of the analysis show that variable institutional ownership, the audit committee and the price to book value a positive effect against the return of the shares, whereas variables of the independent Commissioners, managerial ownership, debt to equity ratio, price earning ratio, and earning per share has no effect against the return of shares. Keywords: Institutional Ownership, Stock Return, The Audit Committee, The Independent Commissioner, Managerial Ownership, Debt to Equity Ratio, Price Earning Ratio, Earning Per Share, Price to Book Value. Abstrak Penelitian ini bertujuan untuk menguji pengaruh corporate governance dan faktor fundamental terhadap return saham. Populasi penelitian ini adalah perusahaan yang terdaftar di Bursa Efek Indonesi dari tahun 2013-2015, sedangkan sampel dalam penelitian ini sebanyak 18 perusahaan. Metode penentuan sampel yang digunakan adalah purposive sampling. Teknik analisis data yang digunakan adalah analisis regresi linier berganda. Hasil analisis menunjukan bahwa variabel kepemilikan institusional, komite audit dan price to book value berpengaruh positif terhadap return saham, sedangkan variabel komisaris independen, kepemilikan manajerial, debt to equity ratio, price earning ratio, dan earning per share tidak berpengaruh terhadap return saham. Kata Kunci: Return Saham, Kepemilikan Institusional, Komite Audit, Komisaris Independen, Kepemilikan Manajerial, Debt to Equity Ratio, Price Earning Ratio, Earning Per Share, Price to Book Value.